Intellectuals and reform in the Ottoman Empire - Taglia, Stefano., author.
1 online resource (ix, 167 pages)
Keywords: “This book uncovers the political and social ideas of the Young Turks at the end of the nineteenth century, during the intellectual phase of the movement. Analysing the life in exile of two of the most charismatic leaders of the Young Turk movement, Ahmed Ryza and Mehmed Sabaheddin, the book unravels their plans for the future of the Ottoman Empire, covering issues of power, religion, citizenship, minority rights, the role of the West, and the accountability of the Sultan. The book follows Ryza and Sabaheddin through their association with philosophical circles, and highlights how their emphasis on intellectualism and elitism had a twofold effect. On the one hand, seeing themselves as enlightened and entrusted with a mission, they engaged in enduring debates, leaving an important legacy for both Ottoman and Republican rule. On the other hand, the rigidity resulting from elitism and intellectualism prevented the conception of concrete plans for change, causing a schism at the 1902 Congress of Ottoman Liberals and marking the end of the intellectual phase. Using bilingual period journals, contemporary accounts, police archives and political and philosophical treaties, this book is of interest to students, scholars and researchers of Middle East and Ottoman History, and Political Science more broadly“--Provided by publisher.